Global impacts of projected climate changes on the extent and aboveground biomass of mangrove forests. (27th September 2022) - Gouvêa, Lidiane P.; Serrão, Ester A.; Cavanaugh, Kyle; Gurgel, Carlos F. D.; Horta, Paulo A.; Assis, Jorge
Abstract: Aim: Over the past 50 years, anthropogenic activities have led to the disappearance of approximately one‐third of the world's mangrove forests and their associated ecosystem services. The synergetic combined effect of projected climate change is likely to further impact mangroves in the years to come, whether by range expansions associated with warming at higher latitudes or large‐scale diebacks linked to severe droughts. We provide an estimate of future changes in the extent and aboveground biomass (AGB) of mangrove forests at global scales by considering contrasting Representative Concentration Pathway scenarios (decade 2090–2100 under RCP 2.6 in line with the Paris Agreement expectations, and RCP 8.5 of higher emissions). Location: Global. Methods: Boosted regression trees fitted occurrence and AGB of mangroves against high‐resolution biologically meaningful data on air temperature, precipitation, wave energy, slope and distance to river Deltas. Results: On the global scale, models produced for present‐day conditions retrieved high accuracy scores and estimated a total area of 12, 780, 356 ha and overall biomass of 2.29 Pg, in line with previous estimates. Model projections showed poleward shifts along temperate regions, which translated into comparable gains in total area, regardless of the RCP scenario (area change RCP 2.6: 17.29%; RCP 8.5: 15.77%). However, biomass changes were dependent on the emission scenario considered, remaining stable or even increasing under RCP 2.6, or undergoing severe losses across tropical regions under RCP 8.5 (overall biomass change RCP 2.6: 12.97%; RCP 8.5: −11.51%). Such losses were particularly aggravated in countries located in the Tropical Atlantic and Eastern Pacific, and the Western and Eastern Indo‐Pacific regions (regions with losses above 20% in overall biomass). Conclusions: Our global estimates highlight the potential effect of future climate changes on mangrove forests and how broad compliance with the Paris Agreement may counteract severe trajectories of loss. The projections made, also provided at the country level, serve as new baselines to evaluate changes in mangrove carbon sequestration and ecosystem services, strongly supporting policy‐making and management directives, as well as to guide restoration actions considering potential future changes in niche availability.